Evaluation of BUMDesa Performance on Village Economy in Bengkalis Regency - Muttaqin, Husnul; Sukma, Doris; Astari, Yanisha Dwi; Dalimunthe, Deliana (Politeknik Negeri Bengkalis, 2024)
This research aims to evaluate the performance of Village-Owned Enterprises (BUMDesa) on the village economyin Bengkalis Regency. The focus of this research was conducted on two independent BUMDesa, namely BUMDesa in KualaAlam Village and Jangkang Village. The research approach used was descriptive qualitative method, where data was collectedthrough in-depth interviews, field observations, and document studies. The analysis in this study aims to describe howBUMDesa contribute to improving the village economy through job creation, increasing community income, as well as localbusiness development. The results show that BUMDesa in both villages studied have a good impact in driving the villageeconomy. In Kuala Alam Village, BUMDesa Kuala Alam plays an active role in the trade, seafood and plantation sectors,which directly increases the income of the local community. While in Jangkang Village, BUMDesa Sejahtera focuses on thetrade and drinking water processing sectors, which also contributes well to the village economy. However, this research alsofound several obstacles faced by BUMDesa, particularly in terms of business management, human resource management. Fromthese findings, it is recommended to increase managerial training for BUMDesa administrators, human resource capacitybuilding, and increase synergy between BUMDesa and local government to improve the effectiveness and sustainability ofBUMDesa programs in supporting village economic development.